Acupuncture Intervention for Plantar Fasciitis: A Case Study - Paulus Suyadi; Leny Candra Kurniawan; Puspo Wardoyo; Ikhwan Abdullah (CV. Inara, 2026)
Plantar fasciitis is a common musculoskeletal disorder characterized by degeneration of the plantar fascia due to repetitive mechanical stress that causes microtears, tissue irritation, and persistent heel pain, which can significantly impair daily activities and quality of life. Although conventional treatments are widely used, acupuncture has increasingly been explored as a complementary therapy for pain management. This study aimed to describe the implementation of acupuncture care for a patient with plantar fasciitis at the Bumi Sehat Acupuncture Clinic in Ubud, Gianyar, Bali. A qualitative case study design was applied to document the clinical management process of acupuncture treatment. The study involved a 55-year-old male patient who underwent six acupuncture treatment sessions during April 2025. Data were collected through the traditional four diagnostic methods of Traditional Chinese Medicine, including observation, listening and smelling, inquiry, and palpation, and were recorded using a structured client data sheet. The patient was diagnosed with plantar fasciitis associated with Cold-Bi syndrome. The therapeutic approach included acupuncture point stimulation combined with moxibustion to remove meridian obstruction, warm the channels, and promote the circulation of Qi and blood. Clinical evaluation across treatment sessions demonstrated progressive improvement in symptoms, including a gradual reduction in plantar pain, decreased heel elevation during walking, improved functional mobility, and resolution of calf stiffness and sleep disturbance. By the fifth treatment session, the patient reported complete relief from pain and regained normal walking ability, which was maintained at the sixth session without recurrence. These findings suggest that structured acupuncture care may contribute to pain reduction and functional recovery in patients with plantar fasciitis. The study provides clinical insight into the application of acupuncture as a complementary therapeutic option in the management of plantar fasciitis.